Analisis Manajemen Risiko Likuiditas Dimasa Pandemi pada lembaga Keuangan Mikro Syariah: (Studi Kasus BMT Maslahah) - Saiful Bakhri; Muhammad Alwi (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2021)
In contrast to banking-based financial institutions, regulations or regulations governing risk management and supervision of Islamic microfinance institutions with cooperative legal entities (BMT) are still minimal and still very weak. BMT as a microfinance institution only relies on internal regulations. This study aims to determine the implementation of liquidity risk management in BMT Maslahah. This study concluded that liquidity risk management at BMT Maslahah is managed professionally and neatly with layered supervision. the risk management process includes identification, measurement, monitoring and control carried out systematically with good risk management standards